FEATURES OF ORGANIZING STUDENTS’ MILITARY-PATRIOTIC EDUCATION IN ENGLISH-SPEAKING COUNTRIES - Skirda, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article analyzes the peculiarities of planning and implementation of the program of military-patriotic education of student youth in English-speaking countries (USA, Great Britain, Canada, and Australia). It was determined that in certain countries, military-patriotic education is implemented within the framework of civic education and is a multifaceted pedagogical phenomenon, the specifics of which development is directly dependent on the practical needs of society at various historical stages of the development of statehood. The purpose of the article is to highlight and analyze the state policy of English-speaking countries (USA, Great Britain, Australia and Canada) in planning and implementing military-patriotic education of schoolchildren and to determine the possibilities of using progressive experience in the national education system. The main tasks of the research are: to study leading scientific studies on the problem of organizing military-patriotic education of schoolchildren in English-speaking countries (USA, Great Britain, Australia and Canada); to determine general patterns and key differences in the development of this area of pedagogical science in English-speaking countries; to analyse the possibilities of using foreign experience of military-patriotic education of schoolchildren in the national educational system. It was determined that the leading idea of modern social and patriotic education of schoolchildren in the USA, Canada, Australia and Great Britain is the idea of forming a socially and politically active citizen by implementing the principles of cultural and historical significance, democratic orientation, social inclusiveness and institutionality. The expediency and prospects of using the experience of military-patriotic education of English-speaking countries in the national educational system are outlined. The scientific novelty of the research is to define a number of general principles of organizing the educational process in Ukraine with the aim of optimizing military-patriotic education based on the experience of civic education in English-speaking countries. The conclusions have confirmed the leading idea of civic (military-patriotic) education in English-speaking countries, the historical prerequisites for the formation of the existing educational strategy. It is highlighted the main mechanisms that determined the purposefulness of using the experience of Anglo-Saxon countries in the national educational system.